(untitled) (Intent Research Scientific Journal, 2023)
This article is aimed at assessing students ’ ability to understand reading when teaching their native language. It emphasizes the importance of assessing literacy skills, studies various methods of assessment, presents the results of recent research, discusses the consequences, and makes recommendations to enhance assessment.